Communities of Practice and the Mediation ofTeachers’ Responses to Standards-based Reform - Gallucci, Chrysan (Education Policy Analysis Archives, 2003)
This paper evaluates the usefulness of a sociocultural approach for analyzing teachers’ responses to the professional learning demands of standards-based reform policies. A policy-oriented case study of the practice of six elementary teachers who worked in two high poverty schools in a demographically changing district in the state of Washington is summarized. Key findings of that study conclude that communities of teaching practice are sites for teacher learning and are mediators of teachers’ responses to standards-based reform. Characteristics of the communities of practice, including their relative strength and openness (to learning), influence the degree to which teachers work out negotiated and thoughtful responses to policy demands. The present paper discusses the efficacy of Wenger’s (1998) theory of learning for the study of policy to practice connections.